POCKET BOOK DIGITAL BERBASIS ETNOMATEMATIKA SEBAGAI BAHAN AJAR SEKOLAH MENENGAH PERTAMA - Ika Herawati; Fredi Ganda Putra; Rubhan Masykur; Chairul Anwar (Journal of Mathematics Education and Science, 2020)
The purpose of this research is to know the development, response and effectiveness of learning using a digital pocket book characterized by Ethnomatematics for junior High School. Research and Development methods. Data Analysis techniques Research on the development of digital pocket books using 2 qualitative and quantitative analytical techniques. Data collection techniques are obtained via polls, interviews, documentation, and tests. The research Model with ADDIE is analysis, design, development, implementation, and Evaluation (evaluation), and assessment. Research conducted at SMPN 7 Metro. The results of this study with students ' responses from the use of digital pocket books characterized by ethnomatematics in small scale tests were obtained on average of 3.49 with "very attractive" criteria and large scale acquired on average of 3.64 With the criteria "very interesting" and the effectiveness of the use of digital pocket Books characterized Ethnomatematics applied in the learning process get a test effect size of 0.59 by medium category. This causes the digital Pocket book to be effective for use in the learning process. Tujuan dari penelitian ini yaitu untuk mengetahui pengembangan, respon maupun efektivitas pembelajaran menggunakan pocket book digital bercirikan etnomatematika untuk sekolah menengah pertama. Metode penelitian yang digunakan (Research and Development). Teknik Analisis DataPenelitian terhadap pengembangan pocket book digital menggunakan 2 teknik analisis Kualitatif dan Kuantitatif. Teknik Pengumpulan Data diperoleh melalui angket, wawancara, dokumentasi, dan tes. Model penelitian dengan ADDIE yaitu analysis (analisis), design (perancangan), development (pengembangan), implementation (implementasi), dan evaluation (evaluasi). Penelitian dilakukan di SMPN 7 Metro. Adappun hasil penelitian ini dengan respon peserta didik dari penggunaan pocket book digital bercirikan etnomatematika dalam uji skala kecil diperoleh rata-rata sebesar 3,49 dengan kriteria “sangat menarik” dan skala besar diperoleh rata-rata sebesar 3,64 dengan kriteria “sangat menarik” Dan tingkat Keefektifan penggunaan pocket book digital bercirikan etnomatematika yang diterapkan dalam proses pembelajaran mendapatkan nilai uji effect size sebesar 0,59 dengan kategori sedang. Hal ini menyebabkan pocket book digital efektif untuk digunakan dalam proses pembelajaran.